Oxygen-Independent Antimicrobial Photoinactivation: Type III Photochemical Mechanism? - Michael R Hamblin; Heidi Abrahamse (MDPI AG, 2020)
Since the early work of the 1900s it has been axiomatic that photodynamic action requires the presence of sufficient ambient oxygen. The Type I photochemical pathway involves electron transfer reactions leading to the production of reactive oxygen species (superoxide, hydrogen peroxide, and hydroxyl radicals), while the Type II pathway involves energy transfer from the PS (photosensitizer) triplet state, leading to production of reactive singlet oxygen. The purpose of the present review is to highlight the possibility of oxygen-independent photoinactivation leading to the killing of pathogenic bacteria, which may be termed the “Type III photochemical pathway”. Psoralens can be photoactivated by ultraviolet A (UVA) light to produce DNA monoadducts and inter-strand cross-links that kill bacteria and may actually be more effective in the absence of oxygen. Tetracyclines can function as light-activated antibiotics, working by a mixture of oxygen-dependent and oxygen independent pathways. Again, covalent adducts may be formed in bacterial ribosomes. Antimicrobial photodynamic inactivation can be potentiated by addition of several different inorganic salts, and in the case of potassium iodide and sodium azide, bacterial killing can be achieved in the absence of oxygen. The proposed mechanism involves photoinduced electron transfer that produces reactive inorganic radicals. These new approaches might be useful to treat anaerobic infections or infections in hypoxic tissue.